2019
DOI: 10.1186/s12895-019-0092-6
|View full text |Cite
|
Sign up to set email alerts
|

Ainhum, a rare mutilating dermatological disease in a female Cameroonian: a case report

Abstract: Background Ainhum is an idiopathic dermatological disease characterized by a progressive constricting ring usually on the fifth toe, which may lead to spontaneous auto-amputation of the affected toe. Timely diagnosis and treatment are the key elements to avert amputations with resultant mutilating deformities, permanent handicaps and psychological sequelae. Though common in African descents, this pathology has not been described in the Cameroonian literature. Herein, we report the case of an adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Ainhum also called as dactylolysis spontanea is derived from the Nago (Brazil) word meaning fissure or Nigerian word meaning ‘to saw or cut’ 1. It is a rare disease chiefly noticed among black Africans and African Americans with male predominance ratio of 2:1 with symmetrical distribution though isolated digits can also be affected 2.…”
Section: Discussionmentioning
confidence: 99%
“…Ainhum also called as dactylolysis spontanea is derived from the Nago (Brazil) word meaning fissure or Nigerian word meaning ‘to saw or cut’ 1. It is a rare disease chiefly noticed among black Africans and African Americans with male predominance ratio of 2:1 with symmetrical distribution though isolated digits can also be affected 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, toenail gangrene can also be found when an excessive volume of local anesthetics is injected circumferentially around the toe [8]. In the contemporary literature, very few good-quality studies have shown a correlation between the use of epinephrine as an adjuvant to local anesthesia and the occurrence of toenail gangrene [18, 19]. However, the use of epinephrine should be avoided in patients with peripheral cardiovascular diseases or increased risks of peripheral ischemia such as Raynaud’s syndrome due to the vaso-constricting effects of epinephrine which may aggravate ischemia [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Ainhum is a rare idiopathic, acquired condition symmetrically involving fifth toes in dark‐skinned individuals of African, Asian, Indian and American origins 1 . It presents with a constrictive ring of fibrous tissue leading to spontaneous phalangeal self‐amputation 2 . The diagnosis is based on clinical criteria: soft tissue constriction, bulbous enlargement of toes, thinning or lysis of phalangeal bones and radiological confirmation 3 .…”
Section: Figurementioning
confidence: 99%
“…1 It presents with a constrictive ring of fibrous tissue leading to spontaneous phalangeal self-amputation. 2 The diagnosis is based on clinical criteria: soft tissue constriction, bulbous enlargement of toes, thinning or lysis of phalangeal bones and radiological confirmation. 3 Ainhum should be distinguished by pseudo-ainhum due to trauma, infections (e.g., syphilis, leprosy and yaws), congenital conditions (e.g., Streeter's dysplasia, keratoderma hereditarium mutilans and palmo-plantar keratoderma), and other diseases such as scleroderma, diabetes, vascular gangrene.…”
mentioning
confidence: 99%